Peranan Blog Guru sebagai Media Interaktif Guru dengan Siswa dalam Pembelajaran IPA: Role of Teacher Blogs as Teacher Interactive Media with Students in Science Learning - Hastuti Wibowo (Universitas Jambi, 2017)
Internet-based interactive media can support the success of learning in a classroom. This study aims to observe the role of blogs as interactive media to improve student learning outcomes. The research used a quasi-experimental method, the independent variable is the use of the teacher's blog and the dependent variable is student learning outcomes. The role of Teacher’s blog is observed on the material of object classification and temperature change. The subjects of this study were students of class VII A and VII E of Xaverius I Middle School in Jambi City. Quantitative data derived from the value of worksheets and written tests after one basic competency cycle is implemented. Data were processed with simple statistics, namely calculating the average value of two basic competencies. The calculated percentage indicates the difference between the average value in the class that does not use the teacher's blog and the class that uses the teacher's blog. The percentage results were analyzed qualitatively referring to theories and results of the previous relevant research. The results of this study indicate an increase of average grade from 75 to 80. Based on the result of the study, it can be concluded that the use of teacher blogs as interactive media is very effective in improving learning outcomes.